Development of learning devices based on discovery learning model on global warming topic to improve student learning motivation and outcome - Mega Safana; Muhammad Zuhdi; Jannatin Ã¢â¬ËArdhuha (Jurnal Pijar Mipa, 2021)
This study aims to develop learning devices based on a discovery learning model on global warming topics that are feasible to improve student physics learning motivation and outcome. The research is a research and development study with the ADDIE model standing for Analyze, Design, Development, Implement, and Evaluate. The developed research instruments are syllabus, Lesson Plan (LP), Student Worksheet (SW), learning video, and test instrument. Meanwhile, data collection instruments include a validation sheet, motivation questionnaire, along pre-test and post-test sheets. Paired sample T-test was used to assess the comparative hypothesis of the two samples' average. The research instruments were developed at the Department of Physics Education Laboratory, Faculty of Teacher Training and Education, University of Mataram and applied in XI MIA 1 class of State Madrasah Aliyah 1 Mataram. Those instruments were syllabus, LP, SW, and test instruments. The developed learning devices based on the discovery learning model were assessed by three expert validators, physics lecturers, resulting in learning devices with "very good" criteria. Hence, the learning devices based on the discovery learning model were feasible to be applied to improve student physics learning motivation and outcome. Based on the implementation of learning devices at State Madrasah Aliyah 1 Mataram, student physics learning motivation was increased by 0.53. In contrast, student physics learning outcome on global warming was improved by 0.47; therefore, both were categorized as "medium". According to paired sample t-test using SPSS 22, the physics learning outcome was 0.000 < 0.005 indicating a significant difference between before and after the learning treatment on students.